Study of nitrate accumulation in herbs of Thymus pulegioides L. for flora of Ukraine - Ya. M. Steshenko; O. V. Mazulin (Zaporozhye State Medical University, 2020)
Thymus pulegioides L. syn. (Thymus ovatus Mill.) of family, Lamiaceae is a fairly common species in Ukraine. Given the literature data, the studied species needs a more thorough study of nitrate accumulation due to the ecological situation in Ukraine, as well as the search for herbal medicinal products with sufficient raw material base and a minimum amount of carcinogenic and harmful substances. The aim of the research: To determine the quantitative content of nitrates in the infusion of grass (1:10) Thymus pulegioides L. flora of Ukraine, using the ionometric method of analysis. Materials and methods. Infusion of Thymus pulegioides L. (1:10) harvested in different regions of Ukraine was studied with the help of the ionometric method of analysis. Results. The accumulation of nitrates was quantified for Thymus pulegioides L. depending on the growing region, using the ionometric method of analysis. The data obtained during the study of the nitrates accumulation in the grass of the species varied from 62.55 ± 7.31 to 232.44 ± 24.11 which do not exceed the generally accepted sanitary norms. Summarizing the study, it was found that the minimum accumulation of nitrates in HRM was found in Poltava and Dnipropetrovsk regions (environment). Conclusions. Given the data obtained, it can be concluded that the study of species of the genus Thymus L. by ionometric method of analysis for nitrate content to control the quality of plant raw materials and drugs based on it was relevant. The central part of Ukraine is a promising and ecologically safe region for the growth of the studied species.